Determinants Of Interest In Investing In The Capital Market (Case Study of Accounting Students at Bandar Lampung University) - Widya Anzelina; Riswan Riswan; Afrizal Nilwan (Cita konsultindo, 2024)
This study aims to identify the impact of motivation, social media influencers, and risk perception on interest in investing in the capital market, with technological progress acting as a moderating variable. The research method used is a quantitative approach using a sample of accounting students at Bandar Lampung University, totaling 81 respondents. The results showed that motivation and social media influencers have a significant influence on interest in investing in the capital market. On risk perception, the results showed a significant negative effect on interest in investing. In addition, technological progress weakens the moderating effect of interest in investing on motivation and risk perception. However, technological progress strengthens the moderating effect of interest in investing in social media influencers.